The impact of work-family conflict on job burnout among community social workers in China. - Dian Song; Jie Zhao; Hainan Wu; Xueyi Ji (PLoS ONE)
In China, for community social workers, work-family conflict has become a common phenomenon that may harm their well-being. Based on the analysis of a survey of community social workers in four cities in China, this study demonstrated that community workers' work-family conflict significantly affects burnout, role overload mediates the relation between work-family conflict and burnout, and cognitive crafting negatively moderates the relation between role overload and burnout. The conclusions validate the job crafting theory and enrich the research on job burnout under the JD-R model. The practical significance of the study is that on the one hand, community and individual workers can effectively alleviate burnout by clarifying their roles. On the other hand, it also reminds managers that they should pay attention to the physical and mental health of social workers to enable them to develop healthily.